Key populations and PLHIVs’ expectation of inclusive HIV/AIDS services: A study of four puskesmas in Yogyakarta and Cilacap - Mellen, Renie; Ida N Faizah; Syafriani; Puji Rahayu; Dwi Maiyanthi; Fithri Zamzam; Fajar Wahyuni; Yanri Subronto; Hasanbasri, Mubasysyir; Retna Siwi Padmawati (BKM Public Health and Community Medicine, 2021)
Objective: To describe the expectation of PLHIV and key populations regarding HIV/AIDS services, especially on pandemic COVID-19. Method: This study conducted a pilot questionnaire survey in Puskesmas Tegalrejo and Mantrijeron, Yogyakarta; and Puskesmas Cilacap Selatan 2, Puskesmas Kesugihan 2, in Cilacap Region, Central Java. The participants were 62 PLWHA and 60 key populations (transgender, male sex workers, IDUs, and sex workers). This paper uses the data from an open-ended item in the questionnaire on respondents' expectation of HIV services in the puskesmas. Result: Both PLHIV and key populations expected equal service, friendly and respectful services without differentiating from other patients. Health workers would be better to know about the diversity of gender and sexual orientation and educate about HIV/AIDS transmission to reduce the fear and stigmatization of the community. In addition, the rotation issues of health workers should not change the quality standards of HIV/aids services. PLHIVs expected that health workers do not disclose their status to others (which should have become the standard of health professionals’ practice) and provide complete support and counseling related to HIV/AIDS with explaining details to the patients. ARV stock is expected to get a one-month stock supply, and queuing for taking drugs. Furthermore, key populations expect flexible time on VCT tests, especially in pandemic COVID-19. Conclusion: The availability and access of puskesmas services for PLHIVs and key populations was significant progress in health care systems. Notes from users emphasize the need for management support in building inclusive services, where health and administrative workers and other puskesmas treated everyone in need equitably.